2014
DOI: 10.1002/hrm.21634
|View full text |Cite
|
Sign up to set email alerts
|

Responses to Discrimination: Relationships Between Social Support Seeking, Core Self‐Evaluations, and Withdrawal Behaviors

Abstract: Drawing from the theory of conservation of resources (Hobfoll, 1989), we examined relationships between social support seeking as a response to perceived discrimination from supervisors, core self-evaluations, and withdrawal behaviors. We further studied how the relationship between social support seeking and withdrawal behaviors was moderated by core self-evaluations. With two different samples, we found, as expected, that social support seeking in response to discrimination from supervisors is positively rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 59 publications
1
25
0
Order By: Relevance
“…Part of the reason leaders are influential in the effectiveness of diversity management strategies is due to their contribution to the organization's diversity climate. In addition to leaders, however, peers (Wagstaff et al, 2015) and employees' direct workgroup (Boehm et al, 2014) can also have a significant impact on the perceived diversity climate of an organization because employees may seek social support from peers in response to discrimination (Wagstaff et al, 2015). Strauss and Connerley (2003) examine how social interactions influence attitudes and find that when employees have contact with diverse others, they have more positive diversity orientations.…”
Section: Diversity Climatementioning
confidence: 99%
“…Part of the reason leaders are influential in the effectiveness of diversity management strategies is due to their contribution to the organization's diversity climate. In addition to leaders, however, peers (Wagstaff et al, 2015) and employees' direct workgroup (Boehm et al, 2014) can also have a significant impact on the perceived diversity climate of an organization because employees may seek social support from peers in response to discrimination (Wagstaff et al, 2015). Strauss and Connerley (2003) examine how social interactions influence attitudes and find that when employees have contact with diverse others, they have more positive diversity orientations.…”
Section: Diversity Climatementioning
confidence: 99%
“…Research has shown that core self-evaluations are related positively to team performance [ 31 ], task and organizational performance [ 32 ], servant leadership and leader effectiveness [ 33 ], life satisfaction, and emotional wellbeing [ 19 ]; on the other hand they are related negatively to work-family conflict [ 34 ], unemployment-related stress [ 35 ], perceived job insecurity [ 36 ], and withdrawal behavior [ 37 ]. Consistently with these findings, we can also expect that core self-evaluations can play a role in affecting retirement-related outcomes (e.g., expected social adjustment, retirement goals and expectations).…”
Section: Core Self-evaluations Affecting Retirement-related Outcommentioning
confidence: 99%
“…We expand the IMCD (Cox, ) and relative deprivation theory (Crosby, ) to consider how a societal contextual factor, specifically changes in employment law, influences the outcomes of perceived racial discrimination at work. Prior research on the consequences of perceived racial discrimination has largely adopted an individual‐lens emphasizing factors such as one's capacity to cope with discrimination (Noh & Kaspar, ), level of self‐esteem (Fischer & Shaw, ), and core self‐evaluations (Wagstaff, Triana, Kim, & Al‐Riyami, in press) as moderators. Furthermore, the IMCD considers individual, group, and organization factors that influence the outcomes of perceived discrimination at work, but it is silent on the role of the broader societal context.…”
Section: Comparison Of Current Study With Previous Meta‐analyses On Pmentioning
confidence: 99%